A Comparative Study of Double Layers Al2O3/Al2O3 and Al2O3/SiO2 Prepared by Microwave and Natural Drying - Ismail, Nur Farhani (International Journal of Integrated Engineering, 2012)
In this work, a comparative study of green multilayered ceramic bodies prepared by natural and microwave drying techniques was investigated. The multilayered ceramic with combination of Al2O3 /Al2O3 and Al2O3/SiO2 samples were prepared via compression method. Alumina powder, Al2O3 with the particle sizes of 90μ,